Synthesis and preliminary radiopharmacological characterisation of an 11C‐labelled azadipeptide nitrile as potential PET tracer for imaging of cysteine cathepsins. (15th May 2019) - Laube, Markus; Frizler, Maxim; Wodtke, Robert; Neuber, Christin; Belter, Birgit; Kniess, Torsten; Bachmann, Michael; Gütschow, Michael; Pietzsch, Jens; Löser, Reik
Abstract : An O ‐methyltyrosine‐containing azadipeptide nitrile was synthesised and investigated for its inhibitory activity towards cathepsins L, S, K, and B. Labelling with carbon‐11 was accomplished by reaction of the corresponding phenolic precursor with [ 11 C]methyl iodide starting from cyclotron‐produced [ 11 C]methane. Radiopharmacological evaluation of the resulting radiotracer in a mouse xenograft model derived from a mammary tumour cell line by small animal PET imaging indicates tumour targeting with complex pharmacokinetics. Radiotracer uptake in the tumour region was considerably lower under treatment with the nonradioactive reference compound and the epoxide‐based irreversible cysteine cathepsin inhibitor E64. The in vivo behaviour observed for this radiotracer largely confirms that of the corresponding 18 F‐fluoroethylated analogue and suggests the limited suitability of azadipeptide nitriles for the imaging of tumour‐associated cysteine cathepsins despite target‐mediated uptake is evidenced. Abstract : An azadipeptide nitrile capable of potent inhibition towards the oncologically relevant cathepsins L, S, B, and K was labelled with carbon‐11 and evaluated by PET imaging in a tumour xenograft mouse model of human mammary carcinoma.